How Graphene Oxide Nanoparticles Can Revolutionize the Concrete Industry - davidson, nathanael; darrell kurniawan, matthew; aria pradana, johannes (Liaison Journal of Engineering, 2023)
One of the most utilized materials for construction is concrete. Concrete is a fairlyinexpensive, strong, and durable material to use for various construction. However, it has been shown that by adding Graphene Oxide Nanoparticles (GONPs) into the concrete mix, it is possible to improve its physical properties and durability. GONPs can be manufactured in various methods, Chemical Vapor Deposition (CVD), Exfoliation (Mechanical or Electrochemical), or Hummers' method. The dispersal of the NPs is also very important to the end physical properties of the dried concrete. Homogenous dispersal can be achieved by High Shear Mixing, Ultrasonication, Surfactant- Assisted Mixing, or Ball Milling. By adding 0.03% by weight of GO to the concrete mix, the compressive strength and the tensile strength both increased by 40% and the total porosity decreased by 13.5%. However, this led to a decrease in the workability by 34.6%. Additionally, this new form of concrete generates overall fewer carbon emissions. Although currently, this new form of concrete is significantly more expensive compared to conventional concrete, it has a longer lifetime and pays back in the long run. Keywords: Concrete; Nanomaterials; Nanoparticles; Graphene; Graphene Oxide; Paper; Journal; Liaison Journal of Engineering; International University Liaison Indonesia;